Serum Uric Acid and Arterial pH in ICU Patients with Sepsis and their Correlation with SOFA Score: A Prospective Observational Study - Govind Shiddapur; Sonali Agarwal (Journal of Clinical and Diagnostic Research)
Introduction: Sepsis remains a critical medical emergency characterised by a dysregulated host response to infection, leading to life-threatening organ dysfunction. Early and accurate prediction of clinical outcomes in septic patients is essential for timely intervention. Common prognostic tools, such as the Sequential Organ Failure Assessment (SOFA) score, are widely used, but additional biochemical markers, such as Serum Uric Acid (SUA) and arterial blood pH, may enhance risk stratification. Aim: To evaluate the role of SUA and arterial pH as prognostic markers in patients with sepsis admitted to the Intensive Care Unit (ICU) and to assess their correlation with SOFA scores. Materials and Methods: A prospective observational study was conducted over a 12-month period in the Department of General Medicine at Dr. D. Y. Patil Medical College, Hospital, and Research Centre, Pimpri, Pune, Maharashtra, India. A total of 150 adult ICU patients diagnosed with sepsis were enrolled. SUA and arterial pH levels were measured on days 0, 1, 2, and 7, alongside serial SOFA scoring. Data were statistically analysed to determine trends and correlations between biomarkers and organ dysfunction severity. Results: SUA levels and SOFA scores showed a statistically significant rising trend from day 0 to day 7 (p-value <0.001), while arterial pH progressively decreased, reflecting increasing metabolic acidosis. A strong positive correlation was observed between uric acid and SOFA scores (r-value=0.74) at day 7, whereas arterial pH showed an inverse correlation (r-value=-0.72). Both biomarkers demonstrated predictive utility for clinical deterioration in septic ICU patients. Conclusion: SUA and arterial pH are valid and readily available biomarkers that are significantly correlated with the SOFA score. Their incorporation into SOFA scoring could enhance early prognostication and facilitate more accurate ICU management.